Limosilactobacillus reuteri - a probiotic gut commensal with contextual impact on immunity - Amanda H. Lee; Daphne Michelle Rodriguez Jimenez; Marlies Meisel (Gut Microbes)
The gut microbiome plays a key role in human health, influencing various biological processes and disease outcomes. The historical roots of probiotics are traced back to Nobel Laureate Élie Metchnikoff, who linked the longevity of Bulgarian villagers to their consumption of sour milk fermented by Lactobacilli. His pioneering work led to the global recognition of probiotics as beneficial supplements, now a multibillion-dollar industry. Modern probiotics have been extensively studied for their immunomodulatory effects. Limosilactobacillus reuteri (L. reuteri), a widely used probiotic, has garnered significant attention for its systemic immune-regulatory properties, particularly in relation to autoimmunity and cancer. This review delves into the role of L. reuteri in modulating immune responses, with a focus on its impact on systemic diseases.